Beginning science teacher cognition and its origins in the preservice secondary science teacher program - Adams, Paul E.; Krockover, Gerald H. (Journal of research in science teaching, 1997)
The objectives of this study were to (a) identify the major tenets of a preservice secondary science education program as expressed by science education faculty, (b) identify knowledge structures that beginning secondary science teachers have constructed about the teaching and learning of science, and (c) identify the correlatives that exist between the first two objectives. The study was grounded in the postulates of teacher cognition in that teachers construct their own schema from their experiences in order to comprehend, plan for, and respond to the dynamics of their classroom. This qualitative study consisted of interviews and observations of beginning science teachers, interviews with science education faculty, and an analysis of the course syllabi of that faculty. Methods of single and cross‐case analytic induction were combined to analyze the data. Based on the data, it may be concluded that aspects of the program, such as student‐centered learning, cooperative learning, general pedagogical knowledge, and pedagogical content knowledge, were adopted into the schema of the beginning teachers; the degree of adoption appeared to be linked to the individual's most significant learning experiences and the constraints of the school situation. © 1997 John Wiley & Sons, Inc. J Res Sci Teach 34: 633–653, 1997.